Foundations of the Descriptive Study of Religions in Muslim History: A Conceptual Analysis. - Akram, Dr. Muhammad (Journal of Islamic Thought and Civilization, 2020)
The classical Muslim scholarly tradition produced an assortment of literature on different religions including a considerable number of descriptive studies, a phenomenon that leaves imposing questions. Most importantly, how a pre-modern civilization was able to generate a tradition of descriptive scholarship on different religions in the absence of conditions such as the western modernity that supposedly factored the emergence of the modern academic study of religion needs to be explored. The current paper ventures to answer this question. It argues that certain features of the Qur’ānic worldview, such as the repeated invitation to observe the signs of God in time and space through travel in the land/across the world and to ponder upon the history of various nations coupled with the exhortation to use reason generated curiosity about different civilizations of the world as well as their religious heritage. Moreover, the Qur’ānic view of the universality of the religious phenomenon as a divine plan also encouraged a sober disposition towards religious others in cases under discussion. On the other hand, the meticulous historiographical techniques and methods for the interpretation of texts developed by Muslim historians, theologians, and jurists afforded the needed methodological apparatus for the said undertaking. The current paper further concludes that the same epistemology and methodological foundations can be appropriated according to/keeping in view the needs of the time to promote a credible study of religion/s in contemporary Muslim societies